(3GdebOeI GdYTeGhjIs - (3YHO GdHGQj GdYTeGhj GdQaGYjs; (3YHO GdHGQj GdYTeGhj GdQaGYj, CHhGdYHGSs
(3ChdgG (B:s
(3bGd GdTjN Gdabjg GdEeGe YHOGdHGQj GdYTeGhj GdQaGYj QMeg Gddg JYGdi SCdfj HYV GdCUObGA Cf CYed oebOeI aj Gdabg Ydi ePgH GdEeGe eGdc s
(3BNQgG (B:s
(3hEPG de JYWd GdeSGLO hGddg CYde hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B544s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs